2020
DOI: 10.1057/s41599-020-00665-x
|View full text |Cite
|
Sign up to set email alerts
|

Consistently biased: documented consistency in self-reported holiday healthfulness behaviors and associated social desirability bias

Abstract: Holiday healthfulness conversations are dominated by overindulgence of consumption and then, largely in reference to resolutions to do better, physical activity, and exercise aspirations. Consistency was found in self-reported agreement with a series of holiday healthfulness statements, across time, holidays (Thanksgiving versus Christmas), and samples of respondents. The largest proportion of respondents displaying social desirability bias (SDB) were found in response to two statements, namely “I will consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Supermarkets have become sites of political and cultural contestation and conflict around public health practices such as mask wearing (Bhasin et al. , 2020; Bir and Widmar, 2020; Makridis and Rothwell, 2020). Consequently, retail workers are put at the “frontline” of ideological, and potentially physical, conflict regarding pandemic health and safety measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supermarkets have become sites of political and cultural contestation and conflict around public health practices such as mask wearing (Bhasin et al. , 2020; Bir and Widmar, 2020; Makridis and Rothwell, 2020). Consequently, retail workers are put at the “frontline” of ideological, and potentially physical, conflict regarding pandemic health and safety measures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the risk of infection exposure, the strain of the ongoing pandemic amplifies customer incivility and misbehavior, which is further exacerbated by the current polarized political and social climate in the United States (Northington et al, 2021). Supermarkets have become sites of political and cultural contestation and conflict around public health practices such as mask wearing (Bhasin et al, 2020;Bir and Widmar, 2020;Makridis and Rothwell, 2020). Consequently, retail workers are put at the "frontline" of ideological, and potentially physical, conflict regarding pandemic health and safety measures.…”
Section: Introductionmentioning
confidence: 99%
“…However, such high delivery rates should be interpreted with caution as multiple studies have highlighted the high level of DRPs in different settings in Jordan [ 21 , 22 ], and such high provision rates could be a result of respondents over-reporting “good behavior”. Such phenomena represent social desirability bias [ 33 ]. However, in a Jordanian study within community pharmacy settings, 76% of the respondents agreed to the idea of providing pharmaceutical care interventions for free and would view that provision of such services can attract business to the pharmacy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study has few limitations. The bias of social desirability (over-reporting of good behavior) [ 33 ], which is inherent in such types of surveys could be a limitation to this study. However, social desirability bias was, to a certain degree, controlled by the anonymous distribution of the survey and the careful formatting of questions minimizing leading questions that would lead to predictable answers.…”
Section: Discussionmentioning
confidence: 99%
“…Lusk and Norwood (2009) proposed an inferred valuation approach to detect and control social desirability bias in the contingent valuation of public and private goods. Bir and Widmar (2020) concluded that cheap talk had limited efficacy with respect to using split sample surveys. Implementation of the inferred valuation method would entail further splitting the surveys into two additional sub-groups.…”
Section: Discussionmentioning
confidence: 99%